Writing for the stage: a relook at dramatic action, language use and cultural conformity in Shona plays - Chigidi, Willie L. (Unisa Publications, 2016)
This article focuses on the challenges that are faced by playwrights who write plays in indigenous languages of Africa for performance on stage with special reference to Shona plays. the article argues that writers of plays, unlike writers of novels, write with the stage and audience in mind since plays are for staging rather than for reading. The major challenge that playwrights who write indigenous languages face therefore is to produce highly entertaining plays that can be staged without offending the cultural sensibilities of theatre goers.